Identification of the drivers of recreation and tourism development in Tajrish district - ali shamai; habib fasihi; mahsa delfannasab (تحقیقات کاربردی علوم جغرافیایی)
Valuable textures play an important role in the development of tourism in various aspects of economic, social, cultural, etc. due to the presence of nostalgic attractions and architectural and cultural relics. The purpose of this study is to examine the factors driving the variables related to recreational plans for the urban tourism development of Tajrish. The collection method is based on library, documentary and field information. . Based on the results of variables such as subsurface development and the establishment of shelter and shelter development in Shohada-Tajrish Hospital, the establishment of a pond of tranquility and development of the Maghsud Beyk river and other variables are independent variables, that is, neither effective nor ineffective. However, creating a cultural and entertainment pole in northern Tehran, promoting eco-tourism, organizing the Emamzadeh Saleh, reviving the trees of Valiasr Street have been considered as variables that have both influencing and influencing the development of tourism in the Tajrish district. However, variables such as neighborhood management, the establishment of a shopping center, the creation of a cultural and entertainment pole in northern Tehran, the expansion of eco tourism surrounding areas of the Tajrish area such as Darband and Derek ... and the development of the Iranian Cinema Museum and ... have been significantly influenced by the strategic area. And determining and strategic in developing the tourism of Tajrish neighborhoods and are considered as key variables.